The Decision to Delivery Interval in Emergency and Non-Urgent Caesarean Sections at King Abdulaziz University Hospital - Khalid H. Sait, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to assess the decision to delivery interval in our obstetric unit in comparison to current recommendations. A retrospective study included an analysis of consecutive non-elective caesarean sections performed at King Abdulaziz University Hospital, Jeddah, Saudi Arabia from January to June 2008. The decision to delivery interval was compared between emergency and non urgent caesarean sections. During the study period, 213 non-elective caesarean sections were performed, 164 were classified as non urgent caesarean (Group 1) and 49 as emergency caesarean (Group 2). The median and inter-quartile ranges in the decision to delivery interval were 62.5 min (45-80) and 41 min (27-68) in Group 1 and 2, respectively (p < 0.001). In the Group 1, 10.3% delivered within 30 min compared to 30.6 % in the Group 2 (p < 0.05). No correlation was found between the decision to delivery interval and the Apgar score at 1 minor 5 min in both groups. Its believed that all centers should set a standard of decision to delivery interval of 30 min. that needs to be achieved in order to reduce maternal anxiety and physician's liability.